Turkish validity and reliability study of Self-Blame Attributions for Cancer Scale: A methodological study - Bahcecioglu Turan, Gulcan; Demir, Nejla; Ozer, Zulfunaz (Cambridge Univ Press, 2026)
Purpose This study aimed to culturally adapt the Self-Blame Attributions for Cancer Scale (SBAC) into Turkish and evaluate its psychometric properties, including validity and reliability.Method This methodological study enrolled 161 patients from both inpatient and outpatient oncology departments of a university hospital during a 1-year observation period (March 2024-March 2025). Participant data were obtained by using 2 instruments: a demographic questionnaire and the adapted Turkish version of the SBAC.Results Confirmatory factor analysis revealed strong factor loadings ranging from 0.670 to 0.850, indicating good item reliability. Model fit statistics demonstrated excellent psychometric properties (chi 2/df = 2.00; root mean square error of approximation = 0.079; Comparative Fit Index = 0.99; standardized root mean square residual = 0.042; Tucker-Lewis Index = 0.98; root mean square residual = 0.042). The scale showed high internal consistency, with a total Cronbach's alpha of 0.93 and subscale alpha coefficients ranging from 0.85 to 0.90. The original 2-factor structure of the SBAC was supported.Conclusion The study confirmed the bidimensional structure (11 items) of SBAC's Turkish version with excellent validity and reliability indices, supporting its cultural and psychometric adequacy for Turkish samples.
Keywords: Nursing; patient; cancer; self-blame; validity; reliability